Susan Booysen, Fees Must Fall: Student Revolt, Decolonisation, and Governance in South Africa (Historia, 2021)
The repercussions of the student revolts of 2015 have had far reaching consequences on policy and governance, Fees Must Fall: Student Revolt, Decolonisation, and Governance in South Africa incorporates an academic analysis of the Fees Must Fallmovement (#FMF) of 2015–2016 through the voices, perspectives and narratives of the students and workers who were at the forefront of the movement. In Part One, Booysens looks at the trajectory of the two weeks in November when the Fees MustFall movements intensified and the repercussions thereof, especially regarding policy and governance. The Fees Must Fall Movement (FMF) stems from the Rhodes Must Fall movement (RMF) which gave way to “Fallism” culture, which had a concertedeffort towards bringing to the fore the intersectional nature of systemic exclusion within South African universities.
Keywords: FeesMustFall; 2015; Decolonisation; Rhodes Must Fall; #FMF